Detection of abandoned mineshafts in the proximity of railways - Drossaert, Francis H (My University, 2008)
This thesis contains the results of a project funded by Network Rail. The mining industry left a legacy of numerous concealed abandoned mineshafts throughout Britain. Decages later an improperly sealed mineshaft can cause subsidence or even collapse. In order to provide a safe reliable railway system, network Rail set itself the target to locate and treat all known mineshafts in the proximity of railways. Several geophysical surveys were commisioned by Network to locate mineshafts, with limited results.
Keywords: Engineering; Geophysics